Filsafat Hukum Utilitarianisme: Konsep dan Aktualisasinya Dalam Hukum di Indonesia - Indra Rahmatullah (ADALAH, 2021)
The purpose of the law is not only about justice as the main paradigm of natural law, but also making legal certainty so that it has a clear barometer as the idea of legal positivism. In the other hand, the purpose of the law must be factual and real to make happiness for most people. The paradigm of Utilitarianism has opened the veil of law to provide something useful and can be felt directly by society. Whatever the policy of the State must guarantee happiness or mutual benefit. Utilitarianism also eliminates the selfishness of mankind, the state, and stakeholders to not only think about their own happiness and destiny but also be encouraged to share with many people.